Delayed symptoms and orthostatic intolerance following peanut challenge. Issue 5 (21st March 2021) - Turner, Paul J.; Ruiz‐Garcia, Monica; Patel, Nandinee; Abrantes, Gonçalo; Burrell, Sarah; Vazquez‐Ortiz, Marta; Skypala, Isabel; Durham, Stephen R.; Boyle, Robert J.
Abstract: Background: Clinical reactions to Oral Food Challenge (OFC) in peanut‐allergic individuals have been well‐characterised, but rates and phenotypes of symptom recurrence beyond the first hour after objective symptoms are less well‐characterised. Objective: To evaluate the rate of new‐onset symptoms occurring at least 1 h after stopping OFC in peanut‐allergic children and adults undergoing peanut‐OFC. Methods: We prospectively collected data relating to adverse events following positive reactions at double‐blind, placebo‐controlled food challenges (DBPCFC) to peanut in children and adults evaluated for eligibility to participate in two clinical trials (NCT02149719, NCT02665793). The trials included people aged 8 to 45 with primary, IgE‐mediated peanut allergy at DBPCFC. The challenge protocol included consumption of a light meal 1 h after reaction. Results: A total of 121 participants (64 children, 57 adults) had immediate, objective symptoms at DBPCFC, 25 (17 children, 8 adults) with anaphylaxis. Thirty‐three (27%) had progression or recurrence of symptoms ≥ 1 h after objective clinical reaction, of whom 8 developed anaphylaxis. In 23 cases, the onset of new symptoms was associated with consumption of a light meal. In eight cases, symptoms were limited to a symptomatic postural fall in blood pressure noted in preparation for discharge, without any other new features of an allergic reaction. Conclusions & Clinical Relevance: Progressive or new‐onset symptoms ≥1 h following initial allergic reaction at OFC are common and can include orthostatic hypotension. Recurrent symptoms may be temporally associated with food consumption.